2017
DOI: 10.31248/jasp2016.029
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of sweet orange (Citrus sinensis) peel meal on the performance of finisher broilers

Abstract: four weeks old broiler chickens of Anak 2000 breed from Imo State Polytechnic Research farm were used to investigate the effect of sweet orange peel meal in broiler rations. The birds were fed on 0%, 2.50%, 5.00%, 7.50% and 10.00% dietary inclusion of sweet orange peel meal as replacement for wheat offals in a 28 day feeding trial. Significant difference between dietary levels of sweet orange peel meal and wheat offals were observed on feed efficiency and weight gain (p<0.05). Increase in dietary levels of swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 5 publications
2
8
2
Order By: Relevance
“…These studies mostly reported the use of citrus pulp (as waste) as feed ingredients or feed supplements to assess carcass quality, meat quality, growth performance, and digestibility of livestock. Few studies have been reported on the use of citrus waste (peel) on livestock performance such as broiler chickens (Ebrahimi et al, 2015;Ahaotu et al, 2017). In addition, we observed that studies on the citrus peel as waste were mainly used to assess its potential as an antimicrobial and antioxidant agent (Ahaotu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These studies mostly reported the use of citrus pulp (as waste) as feed ingredients or feed supplements to assess carcass quality, meat quality, growth performance, and digestibility of livestock. Few studies have been reported on the use of citrus waste (peel) on livestock performance such as broiler chickens (Ebrahimi et al, 2015;Ahaotu et al, 2017). In addition, we observed that studies on the citrus peel as waste were mainly used to assess its potential as an antimicrobial and antioxidant agent (Ahaotu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The poultry industry is one of the fast means of providing the much needed animal protein to the teeming populace. It has been suggested that the expansion of the Nigeria poultry holds the greatest promise of bridging the animal protein gap in the country within the shortest possible time (Ahaotu et al, 2017a). Some agro-industrial by-products like Bambara nut, feather meal, rice offal, brewer's dried grain have been used in poultry diets to replace cereals (Ahaotu, 1999;Ahaotu et al, 2010aAhaotu et al, , b, 2015Ahaotu et al, , 2016aAhaotu et al, , b, 2012a.…”
Section: Introductionmentioning
confidence: 99%
“…The high cost of feed in most tropical countries clearly indicates that the production of cereal grains for livestock business is grossly inadequate (Ahaotu et al 2017). Furthermore, the stiff competition existing between humans and animals over the available grains has resulted in the near collapse of the poultry industry in Nigeria (Ayo-Enwerem et al, 2017).…”
Section: Introductionmentioning
confidence: 99%